Pengujian Ekstrak Kulit Buah Jengkol Sebagai Pestisida Nabati Pada Keong Mas : Examination Of Jengkol Fruit Peel As Natural Pesticide Of Mas Snail - Nurmaya; Amanda Firmansyah; Rosanna (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2022)
Mas snail (Pomacea canaliculata) is one of the pests that attack paddy plant. These pests eat young plants until they are ready to be harvested. Therefore an effective method needed to control it. One method that can be used is plant extracts from jengkol fruit peel which can be used as a natural pesticide. The active compounds of saponins in jengkol fruit peel can reduce the activity of digestive enzymes and absorption of snail food. The purpose of this study was to determine the effectiveness of jengkol (Pithecellobium jiringa) peel extract as a natural pesticide against mas snail (Pomacea canaliculata). The research was carried out by making an extract consisting of 1 kg of jengkol fruit peel that blended together with 1 L of distilled water. The extract was then filtered and applied to the golden snail with different concentrations for each treatment, namely 0ml/L (M0), 4ml/L (M1), 5ml/L (M2), 6ml/L (M3) and 7ml/L (M4). The results showed that jengkol fruit peel extract was effective in controlling golden snail pests with the best concentration of 7 ml/L.